Термодинамически обоснованный энергосберегающий потенциал установки АВТ 12/2 в режиме работы без вакуумного блока - Товажнянский, Леонид Леонидович; Ульев, Леонид Михайлович; Мельниковская, Лиана Александровна; Зулин, Борис Дмитриевич (НТУ "ХПИ", 2010)
The energy saving potential for AVDU A12/2 crude distillation unit with working without vacuum column was defined. Pinch-analysis methods use allows us to decrease the useful power which consuming by process at 78 % that is 34 MW. The cold utilities will disappear almost completely with pinch retrofit. Annual profit from implementing this project will be the value 3387900 USD and payback period will not exceed 1 year.
Keywords: энергоносители; электроэнергия; топливо; нефтепереработка; атмосферно-вакуумная трубчатка; теплообмен; экстракция данных; установка АВТ А12/2; энергосбережение; первичная переработка нефти; нефтеперерабатывающая промышленность